Incidence of adult tonsillectomy for hypertrophic indications in Southwest Finland - Sjöblom, Henrik M.; Knubb, Jenny C.; Kauko, Tommi; Pulkkinen, Jaakko; Piitulainen, Jaakko M. (Informa UK Limited, 2026)
Background
Large palatine tonsils cause a variety of symptoms including obstructive sleep apnea and snoring. In adults, the prevalence of tonsillar hypertrophy remains uncertain.
Aims
We estimated the incidence of tonsillectomy for adult palatine tonsillar hypertrophy using population data and retrospective patient charts.
Material and Methods
Patient data were retrospectively collected between 2004 and 2018 in the Hospital District of Southwest Finland. Adult patients with tonsil hypertrophy, obstructive sleep apnea or mouth breathing/snoring as an indication for surgery were included. Data were verified from patient charts. To determine in adults the incidence of tonsillectomy for tonsillar hypertrophy, the number of surgeries was compared to population data.
Results
The incidence of tonsillectomy for adult tonsillar hypertrophy was 8.49 per 100000 person-years. In our hospital district, 9.5% of adults who underwent tonsil surgery had tonsillar hypertrophy. The incidence rate reduced with age. The most common indication for surgery of hypertrophic tonsils was snoring (30.8%). In this study, 12.7% of patients with asymmetric tonsils had malignancy with the most common being lymphoma.
Conclusions and Significance
Symptomatic adult tonsil hypertrophy remains rare. In adults, tonsil asymmetry should invoke a suspicion of lymphoma. Even during adulthood, as age increases, tonsillar hypertrophy becomes less common.